Ekstrak Kulit Kayu Manis sebagai Inhibitor Korosi pada Baja Karbon dalam Lingkungan Air Laut - Ihtisyamuddin .; Selvie Diana; Irwan Irwan (Jurnal Teknologi, 2023)
The utilization of cinnamon bark extract as a corrosion inhibitor of low-carbon steel in seawater media was studied. The purpose of the research was to investigate the effect of cinnamon bark extract concentration and immersion time on the corrosion rate of carbon steel in seawater environments. The study was conducted at different concentrations of cinnamon bark extract, i.e. 0,1, 2, 3, 4, and 5 mL/L, and immersion time. i.e. 5, 10, 15, 20, and 25 days. The research was investigated using standard laboratory corrosion testing material according to ASTM G31-72. The effect of cinnamon bark extract and immersion time was examined on the corrosion rate and efficiency inhibition. The results showed that the concentration of cinnamon bark extract and immersion time influenced the corrosion rate of carbon steel in seawater media. Increasing of concentration of cinnamon bark extract and immersion time decrease of corrosion rate. The lowest corrosion rate obtained was 0.0492 mpy which was received at a cinnamon bark extract of 5 mL/L and immersion time of 25 days. The efficiency inhibition of cinnamon bark extract was increased with increasing immersion time. The highest efficiency was 54,48%.